Current trends in the epidemiology and management of viral co-infections and comorbidities in Africa: a systematic review - Axel Cyriaque Ambassa; Axel Cyriaque Ambassa; Fabrice Chethkwo; Elise Guiedem; Brenda Grace Lele; Brenda Grace Lele; Ironne Valdese Ayemfouo Fofou; Ironne Valdese Ayemfouo Fofou; Marceline Djuidje Ngounoue; Marceline Djuidje Ngounoue; Marceline Djuidje Ngounoue (Frontiers in Virology)
BackgroundViral infections, particularly hepatitis B virus (HBV), hepatitis C virus (HCV), hepatitis Delta virus (HDV), and human immunodeficiency virus (HIV), pose significant public health challenges worldwide, especially in low- and middle-income countries (LMICs) in Africa. The diagnosis and management of these diseases become increasingly complicated when viral co-infections are present. This review aims to explore current trends in the epidemiology and management of viral co-infections and comorbidities in LMICs.MethodsA systematic review was conducted following the PRISMA-ScR (Preferred Reporting Items for Systematic and Meta-Analyses extension for Scoping Reviews) guidelines. A thorough literature search was performed across two databases: PubMed and Google Scholar. A total of 390 records were identified from PubMed, and approximately 17,000 from Google Scholar for studies published between 2015 and 2025. After removing duplicates and applying eligibility criteria, 50 articles from PubMed were screened based on their titles, abstracts, and full texts. Of these, 15 studies that met the inclusion criteria were selected for data extraction and synthesis, using a data extraction form to organize the relevant information.ResultsOut of the 50 screened studies, 15 met the inclusion criteria and were included in the final analysis. These studies primarily focused on co-infections of HIV with HBV and HCV. The prevalence rates of HBV among individuals living with HIV varied from 1.1% to 9.1% in cross-sectional studies, with notable populations including pre-ART patients and pregnant women. One study reported a particularly high rate of HCV co-infection at 66.6% among intravenous drug users. However, no eligible studies were available for HBV-HDV co-infection or treatment-specific outcomes.ConclusionThis review highlights the significant burden and variability of HIV co-infections in Africa, particularly the co-infection of HIV with HBV. The findings emphasize the necessity for integrated screening and management strategies, as well as the need for further research to optimize interventions and improve health outcomes for individuals with co-infections.